2007
DOI: 10.5005/jcdp-8-2-89
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Finishing and Polishing Systems on the Surface Roughness of Different Composite Restorative Materials

Abstract: Aim:The purpose of this in vitro study was to examine the effect of two different finishing systems on the o surface roughness of different types of composite restorative materials. Methods and Materials:Thirty specimens, 8 mm in diameter and 3 mm in depth, were prepared using a microfill composite (Clearfil ST, Kuraray Co. Ltd., Osaka, Japan), a hybrid composite (Clearfil AP-X, Kuraray Co. Ltd., Osaka, Japan), and a packable composite (Clearfil Photo Posterior, Kuraray Co. Ltd., Osaka, Japan) cured against a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Surface roughness, given as the roughness value—Ra, does not present sufficient information about gloss or tooth appearance after wetting, because subjective feelings depend on many other factors [ 15 ]. This value however corresponds with smoothness which is responsible for dental plaque accumulation, discoloration of material surface and as a consequence risk of secondary caries, and inflammation of marginal gingiva [ 4 , 5 , 8 12 , 16 , 17 ]. Bollen et al proved that surface roughness at the level 0.2 μ m is sufficient to reduce adhesion of bacteria to the filling surface [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness, given as the roughness value—Ra, does not present sufficient information about gloss or tooth appearance after wetting, because subjective feelings depend on many other factors [ 15 ]. This value however corresponds with smoothness which is responsible for dental plaque accumulation, discoloration of material surface and as a consequence risk of secondary caries, and inflammation of marginal gingiva [ 4 , 5 , 8 12 , 16 , 17 ]. Bollen et al proved that surface roughness at the level 0.2 μ m is sufficient to reduce adhesion of bacteria to the filling surface [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The variations in color stability observed among the tested materials could also be attributed to the differences in filler/resin ratio (Table 1 ). Previous studies have reported that resin composites with a low filler/resin ratio, which often corresponds to a lower viscosity, may exhibit reduced polishability and color stability [ 31 33 ]. Moreover, the observed color change can also be attributed to the silane agent used.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, this finishing and polishing system had been considered to be the most efficient when comparing to other systems [18]. During finishing procedure the resin matrix is initially removed due to its lower hardness while the filling particles are exposed and subsequently dislocated from the resin matrix, thus increasing the surface roughness [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies which evaluated the surface roughness of composite resins after finishing and polishing procedure had concluded that the degree of material finishability depends on two factors: the size of the filling particles of the composite resin and the size of abrasive particles of the finishing system [19,20]. In this study, we tested microhybrid composite resins composed of zirconium/silicium and barium/silicium particles with dimensions between 0.01-3.5 µm and nanohybrid composite resins based on zirconium/silicium, barium glass fillers and silicon dioxide particles with dimensions between 20-50 nm.…”
Section: Discussionmentioning
confidence: 99%